El delito de abuso de poder económico en el Perú: desafios en su tipificación como delito y en el estándar probatorio en sede administrativa - Vinelli Vereau, Renzo (Pontificia Universidad Católica del Perú, 2025)
The crime of abuse of economic power in Peru has undergone a fluctuating regulatory evolution, reflecting the tension between criminal intervention and administrative regulation in economic matters. Its criminalization, currently contained in article 232 of the Criminal Code, responds to the need to punish anticompetitive practices of absolute prohibition. In this context, the competence of INDECOPI to previously establish the existence of an administrative infringement introduces a referral mechanism that conditions the criminal prosecution.

El delito de abuso de poder económico en el Perú ha experimentado una evolución normativa fluctuante, reflejando la tensión entre la intervención penal y la regulación administrativa en aspectos de índole económico. Su tipificación, actualmente recogida en el artículo 232 del Código Penal, responde a la necesidad de sancionar prácticas anticompetitivas de prohibición absoluta. En este contexto, la competencia del INDECOPI para establecer previamente la existencia de una infracción administrativa introduce un mecanismo de remisión que condiciona la persecución penal.
The crime of abuse of economic power in Peru: Challenges in its classification as a crime and the standard of proof in administrative proceedings
Keywords: Abuse of economic power; Free competition; Criminal law in white; Absolute prohibitions; Abuse of dominant position; Abuso de poder económico; Libre competencia; Ley penal en blanco; Prohibiciones Absolutas; Abuso de posición de dominio; https://purl.org/pe-repo/ocde/ford#5.05.00